COMMUNICATION AND INTERPERSONAL SKILLS IN PRACTICE OF PEDIATRIC DENTISTRY - Padalka, A.I.; Trufanova, V.P.; Polishchuk, T.V.; Kostenko, V.G.; Sheshukova, O.V. (World of Medicine and Biology, 2018)
This article aims at analyzing the main approaches and principles of professional communication between pediatric dentists and their patients. Communication skills are one of the major competences in the pediatric clinical practice. Dealing with children of all ages, the dentist have to take into account the level of child’s development, to choose or to design a special approach to each of the patients, to demonstrate child-friendly and encouraging attitude. The ability to involve the parents into trust relationship and to build up cooperation is one of determinant factors in reaching successful treatment outcomes.
Keywords: children; pediatric dentist; communicative competence; communication